CLAUSAL ADJUNCTS OF ROMANCE LANGUAGES – A CORPUS-DRIVEN COMPARISON – - BODOC, Alice (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Clausal Adjuncts of Romance Languages – a Corpus-Driven Comparison. Continuing the traditional comparative analysis of Romance languages, the present paper brings evidence for the fact that the syntactic configuration (the word order) of a Romance complex sentence (henceforth CS) with clausal adjuncts is the result of many competing forces. The analysis is based on an original media discourse corpus, collected from three Romance varieties (Romanian, Italian, and French), and the focus will be both on the word order of the temporal, causal, and concessive adjuncts (their occurrence in sentence-initial, in sentence-final position, sometimes even in sentence-middle position), and on the comparative analysis of the results. What I intend to prove is that the ordering of a CS in the three Romance languages is motivated by three types of factors: discourse pragmatics, semantics, and parsing. Article history: Received 8 July 2021; Revised 8 November 2021; Accepted 20 November 2021; Available online 31 March 2022; Available print 31 March 2022. REZUMAT. Adjuncții propoziționali din limbile romanice – o analiză de corpus din perspectivă comparativă. Continuând tradiția analizelor comparative dedicate limbilor romanice, lucrarea de față își propune să prezinte o serie de dovezi în favoarea ipotezei potrivit căreia configurația sintactică (ordinea constituenților) a structurilor sintactice complexe cu adjuncți din limbile romanice este rezultatul mai multor forțe concurente. Analiza are la bază un corpus original de texte aparținând discursului mediatic contemporan, colectat din trei varietăți romanice (limba română, limba italiană și limba franceză) și se concentrează, pe de o parte, asupra descrierii poziției adjuncților temporali, cauzali și concesivi (de la începutul, sfârșitul sau chiar din mijlocul structurii sintactice complexe), iar, pe de altă parte, asupra comparării rezultatelor obținute în cazul celor trei limbi investigate. Scopul unui astfel de demers este de a demonstra că topica acestor structuri este motivată, atât în limba română, cât și în celelalte două limbi-surori, de trei tipuri de factori: pragmatico-discursivi, semantici și morfosintactici. Cuvinte-cheie: adjuncți propoziționali, analiză morfosintactică, configurație sintactică, limbi romanice